Cholangiocarcinoma Derived from Remnant Intrapancreatic Bile Duct Arising 32 Years after Congenital Choledochal Cyst Excision: A Case Report - Kentaro Ishikawa; Sadahisa Ogasawar; Tetsuhiro Chiba; Dai Sakamoto; Naoya Kanogawa; Tomoko Saito; Tenyu Motoyama; Eiichiro Suzuki; Yoshihiko Ooka; Harutoshi Sugiyama; Akinobu Tawada; Yuji Sakai; et al. (Case Reports in Oncology, 2015)
We report a rare case of a 46-year-old woman with cholangiocarcinoma derived from remnant intrapancreatic bile duct arising 32 years after the excision of a congenital choledochal cyst. She had undergone anastomosis of the choledochal cyst and duodenum at birth, excision of the choledochal cyst and hepaticoduodenostomy with jejunal interposition at 14 years of age as well as the excision of an infectious cyst around the anastomosis site at 21 years of age. At 29 years of age, she was diagnosed with a chronic hepatitis C virus (HCV) infection and was referred to our hospital for treatment. She did not consent to interferon-based therapy against the HCV infection. At 46 years of age, she experienced epigastric discomfort. A dynamic CT revealed multiple tumors in the liver, a tumor in the head of the pancreas as well as lymph node metastases in the mediastinum and abdominal cavity. A liver tumor biopsy revealed adenocarcinoma, and she was clinically diagnosed with cholangiocarcinoma derived from remnant intrapancreatic bile duct with multiple metastasis in the liver and lymph node metastasis. She requested palliative therapy and eventually died during the treatment course. The autopsy specimen revealed a tumor in the head of the pancreas, and on the basis of local existence and the pattern of metastasis, it was confirmed as cholangiocarcinoma derived from remnant intrapancreatic bile duct. A microscopic examination revealed a poorly differentiated adenocarcinoma. This report provides information on a case of cholangiocarcinoma derived from remnant intrapancreatic bile duct arising after the excision of congenital choledochal cyst that was assessed pathologically.